THE SIYASAH SHAR'IYYAH PERSPECTIVE OF NAJIB'S TRANSFORMATIONAL AGENDA IN MAKING MALAYSIA INTO A HIGH INCOME NATION - Lukman Thaib (Share: Jurnal Ekonomi dan Keuangan Islam, 2017)
Malaysia is a country that since its independence has endeavored to practice democratic governance. In line with this, it seeks to ensure that the Malaysian government is representative of the will of the people. To achieve this, there must be in place numerous mechanisms to ensure accountability and transparency while also ensuring that it has an "ear to the ground" so to speak. Dato' Sri Mohd Najib believed that transformational leadership posts the leader in the role of mentor whereby he able to designate responsibilities to his followers as a means to achieve self-actualization which is a positive means of promoting team-building efforts. To achieve the goals shared between him as a country's leader and Malaysian peoples as his followers, he believed that inspirational motivation is needed, as it provides meaning to achieving this shared vision on "how to make Malaysia as a high-Income Nation by 2020"?. PM Mohd Najib has been successful in articulating a compelling vision of Malaysia's future and tied a high-income nation's vision to Malaysian citizen values, and ultimately he is capable of being a "transformational leader". It is to this end that this paper is committed, namely to analyzing the important role played by PM Mohd Najib towards outlining a clear vision of national development and whether this is in line with the objective of maqasid shar'iyyah. For this, PM. Mohd Najib appears to have opted to pursue "The Government Transformation Programme (GTP)" to address seven key areas concerning Malaysia's interest in realizing Malaysia's vision to become a high-income nation by 2020. ========================================================================================================Malaysia adalah negara yang sejak kemerdekaannya telah berupaya untuk melaksanakan tata kelola pemerintahan yang demokratis. Sejalan dengan ini, ada usaha untuk memastikan bahwa pemerintah Malaysia merupakan perwakilan dari kehendak rakyat. Untuk mencapai hal ini, harus terdapat banyak mekanisme untuk menjamin akuntabilitas dan transparansi sekaligus juga memastikan bahwa ia memiliki 'telinga ke tanah'. Dato' Sri Mohd Najib yakin bahwa kepemimpinan transformasional mengganggap pemimpin sebagai mentor yang mampu menunjuk tanggung jawab kepada anggotanya sebagai sarana untuk mencapai aktualisasi diri yang merupakan sarana positif dalam mempromosikan upaya pembangunan tim. Untuk mencapai tujuan bersama antara Dato' Sri Mohd Najib sebagai pemimpin negara dengan bangsa Malaysia sebagai pengikutnya, ia percaya bahwa motivasi inspirasional diperlukan sebagai makna untuk mencapai visi bersama tentang "bagaimana membuat Malaysia sebagai negara berpenghasilan tinggi pada tahun 2020"? PM Mohd Najib telah berhasil dalam mengartikulasikan visi yang menarik dari masa depan Malaysia, dan berhasil mengikat visi pendapatan nasional yang tinggi untuk kepentingan warga Malaysia, dan akhirnya ia mampu menjadi 'pemimpin transformasional'. Ini adalah tujuan penulisan jurnal, yaitu untuk menganalisis peran penting yang dimainkan oleh PM Mohd Najib terhadap penguraikan visi yang jelas dari pembangunan nasional dan apakah ini sejalan dengan tujuan shar'iyyah maqasid. Untuk itu, PM Mohd Najib tampaknya telah memilih untuk mengejar 'Program Transformasi Pemerintah Program untuk menyelesaikan tujuh bidang utama mengenai kepentingan Malaysia dalam mewujudkan visi Malaysia untuk menjadi bangsa yang berpenghasilan tinggi pada tahun 2020.